2008
DOI: 10.1121/1.2913046
|View full text |Cite
|
Sign up to set email alerts
|

Identification and discrimination of bilingual talkers across languages

Abstract: This study investigated the extent to which language familiarity affects the perception of the indexical properties of speech by testing listeners' identification and discrimination of bilingual talkers across two different languages. In one experiment, listeners were trained to identify bilingual talkers speaking in only one language and were then tested on their ability to identify the same talkers speaking in another language. In the second experiment, listeners discriminated between bilingual talkers acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
126
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(147 citation statements)
references
References 45 publications
18
126
2
1
Order By: Relevance
“…First, there was an overall effect of native language: native listeners performed better than secondlanguage listeners (Korean-English bilinguals hearing English voices) or listeners unfamiliar with the language (English listeners hearing Korean voices). While previous studies showed that listeners learn to recognize unfamiliar voices better when they speak the language or dialect of the talker (Goggin et al, 1991;Perrachione et al, 2011;Winters et al, 2008), we demonstrate that listeners with lengthy exposure, but without native-speaker status, had increased difficulty recognizing voices in their second language. Our second major discovery was that within bilinguals, age of second-language acquisition impacted performance on voice learning.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…First, there was an overall effect of native language: native listeners performed better than secondlanguage listeners (Korean-English bilinguals hearing English voices) or listeners unfamiliar with the language (English listeners hearing Korean voices). While previous studies showed that listeners learn to recognize unfamiliar voices better when they speak the language or dialect of the talker (Goggin et al, 1991;Perrachione et al, 2011;Winters et al, 2008), we demonstrate that listeners with lengthy exposure, but without native-speaker status, had increased difficulty recognizing voices in their second language. Our second major discovery was that within bilinguals, age of second-language acquisition impacted performance on voice learning.…”
Section: Discussionmentioning
confidence: 48%
“…Recent studies suggest a relationship between knowing a language and ability to identify talkers in that language (Goggin et al, 1991;Johnson et al, 2011;Perrachione et al, 2011;Sullivan and Schlichting, 2000;Winters et al, 2008). This radically departs from a viewpoint that speech processing operates over an abstract set of symbols.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, accuracy ranged from 52% to 85% across all 65 normal-hearing individual listeners. Substantial individual variability is also observed in other studies investigating voice recognition (e.g., Winters et al, 2008). Such individual differences pose a special problem for voice lineups in forensic cases: Evidently, earwitnesses vary tremendously in their competency to identify speakers in voice parades.…”
Section: Introductionmentioning
confidence: 71%
“…Namely, listeners have more difficulty identifying talkers in unfamiliar languages compared to their native language, a phenomenon known as the language familiarity effect (Perrachione et al, 2011;Perrachione et al, 2009). This advantage is assumed to arise because native speakers can access talker-idiosyncratic phonetic variation in their native language (e.g., Remez et al, 1997;Winters et al, 2008). For this reason, we compared native-Mandarin versus native-English listeners' performance in identifying Mandarin, English, and Spanish talkers.…”
Section: Methodsmentioning
confidence: 99%